Effect of post-fermentation and packing stages on the volatile composition of Spanish-style green table olives. (15th January 2018) - Sánchez, Antonio Higinio; López-López, Antonio; Cortés-Delgado, Amparo; Beato, Víctor Manuel; Medina, Eduardo; de Castro, Antonio; Montaño, Alfredo
Highlights: More than 130 compounds were identified in Spanish-style green table olives. The contents of volatiles were affected by post-fermentation and packing stages. Significant differences in volatile compounds between olive cultivars were found. Lipid oxidation likely occurred as a result of packing in the cultivars studied. Abstract: The volatile profile of Spanish-style green table olives after fermentation and the changes in volatile compounds that occurred as a result of the post-fermentation and subsequent packing stage were explored by solid phase micro-extraction (SPME) and gas chromatography coupled to mass spectrometry (GC–MS). Three olive cultivars (Manzanilla, Gordal, and Hojiblanca) were processed and olive samples were taken at three different times throughout the elaboration: after fermentation, after post-fermentation, and after packing. A total of 132 volatile compounds were identified, including 10 phenols, 25 alcohols, 11 acids, 39 esters, 8 hydrocarbons, 14 carbonyl compounds, 17 terpenes, and 6 other compounds. A varying number of compounds from each chemical family underwent significant changes because of the post-fermentation and packing stages. Among them, some typical reaction products of lipid oxidation (e.g. ( E )-2-decenal and ( E, E )-2, 4-decadienal) increased with the post-fermentation in Manzanilla cultivar, and also as a result of packing in all three cultivars.